Review of Simultaneous Double Stenting Using Endoscopic Ultrasound-Guided Biliary Drainage Techniques in Combined Gastric Outlet and Biliary Obstructions - Hao Chi Zhang; Monica Tamil; Keshav Kukreja; Shashideep Singhal (Korean Society of Gastrointestinal Endoscopy, 2020)
Concomitant malignant gastric outlet obstruction and biliary obstruction may occur in patients with advanced cancers affecting these anatomical regions. This scenario presents a unique challenge to the endoscopist in selecting an optimal management approach. We sought to determine the efficacy and safety of endoscopic techniques for treating simultaneous gastric outlet and biliary obstruction (GOBO) with endoscopic ultrasound (EUS) guidance for biliary drainage. An extensive literature search for peer-reviewed published cases yielded 6 unique case series that either focused on or included the use of EUS-guided biliary drainage (EUS-BD) with simultaneous gastroduodenal stenting. In our composite analysis, a total of 51 patients underwent simultaneous biliary drainage through EUS, with an overall reported technical success rate of 100% for both duodenal stenting and biliary drainage. EUS-guided choledochoduodenostomy or EUS-guided hepaticogastrostomy was employed as the initial technique. In 34 cases in which clinical success was ascribed, 100% derived clinical benefit. The common adverse effects of double stenting included cholangitis, stent migration, bleeding, food impaction, and pancreatitis. We conclude that simultaneous double stenting with EUS-BD and gastroduodenal stenting for GOBO is associated with high success rates. It is a feasible and practical alternative to percutaneous biliary drainage or surgery for palliation in patients with associated advanced malignancies.